Communication Styles of Human-Machine Interaction in the ChatGPT - Ningsih, Ayu Setia; Rohmah, Galuh Nur (Indonesian Journal of EFL and Linguistics, 2024)
This research aims to analyze the communication style of Human-machine interaction based on ChatGPT 3.5 to understand the pros and cons, as well as potential improvements in the implementation of this technology. Humans have limitations in processing complex information. The emergence of machines helps humans complete work, and many machine features provide solutions. This research found out human-machine interaction, focuses on communication and using cooperative principles that have four maxims: maxim quantity, maxim quality, maxim relation, and maxim manner are some of the divisions that will be sought in human-machine interaction. The research uses a qualitative method by using a chatbot as a GPT version 3.5 chat that is then given a command. Then, the data is collected and analyzed. From this analysis, human-machine interaction qualitatively has good performance but has a deficiency in maximum quantity due to too much information given. The outcome of the violation of the maxim quantity that stands out requires self-interpretation where the statements correspond to the question. This research is expected to help develop human-machine interaction technology primarily in business.